The multiplicative zagreb coindices of graph operations - Nacaroglu Y.; Maden, A. Dilek (Utilitas Mathematica, 2017)
In this paper, we present some lower bounds for the first and second multiplicative Zagreb coindices of several graph operations such as union, join, corona product, tensor product, Cartesian product, strong product, lexicographic product in terms of the first and second multiplicative Zagreb coindices and the multiplicative Zagreb indices of their components.